Opaepupu, a new genus and species of bivalve-associated shrimp (Decapoda: Caridea: Palaemonidae) from Hawai’i - Anker, Arthur; Grave, Sammy De (Zootaxa, 2021)
A new palaemonid shrimp genus, Opaepupu gen. nov., is established to accommodate a new species of bivalve-associated shrimp, Opaepupu huna sp. nov. from Hawaii. A single mated pair, the female holotype and the male allotype, were found inside the trapezid bivalve Trapezium oblongum (Linnaeus, 1758) at a depth of 14 m in Kâne’ohe Bay, Hawai’i. The new genus is characterised by the rostrum being proximally broad, distally pointed, mid-dorsally carinate, and non-dentate; the anterolateral margin of the carapace without supraorbital, hepatic or epigastric teeth, but with a strong sharp antennal tooth; the sixth pleonite posteriorly unarmed; the telson medially depressed, with the dorsal surface armed with two pairs of submarginal cuspidate setae and with the posterior margin armed with two pairs of spiniform setae; the distolateral angle of the first article of the antennular peduncle without a sharp tooth; the mandible without a palp; the maxillular palp furnished with one long stiff seta dorsal to a small tooth-like extension; the first maxilliped without a palp; the third maxilliped not being operculate; the second pereiopods moderately robust, relatively slender, subequal, subsymmetrical, with simple teeth on the cutting edges of the fingers; the ambulatory pereiopods being slender, each ending in an elongate biunguiculate dactylus; and the uropodal exopod with a faint diaeresis and greatly reduced distolateral spiniform seta. The phylogenetic position of Opaepupu gen. nov. remains unclear, although it does not appear to be closely related to other bivalve-associated palaemonid genera.